Numerical Optimization of Plasmonic CuO-Based Semi-Transparent Thin Film Solar Cell Device via L9 Taguchi Orthogonal Array Method and ANOVA - J. Husna,; N.A. Jamil,; K.S. Siow,; T. R. Lenka,; H. Kumar,; P. Chelvanathan,; M. A. Mohamed,; A.R. Zain,; J. Sampe,; P. S. Menon, (International Journal of Integrated Engineering, 2024)
The future of smart cities and energy-efficient infrastructures are very much dependent on photovoltaic materials that are sustainable, functional and affordable. In this context, copper oxide (CuO)-based solar cells provide the advantages of energy harvesting coupled with semi-transparent light transmission. In this work, a p-CuO thin film layer was used together with n-doped zinc oxide (ZnO), Al-doped zinc oxide (AZO) and indium tin oxide (ITO) to form a semi-transparent thin film solar cell (STFSC) model developed using SCAPS-1D and optimized using Taguchi L9 orthogonal array and analysis of variance (ANOVA). Optimized parameters for the CuO absorber and ZnO window/buffer layers were obtained for the best values for doping variation level and layer thickness. With the optimized design parameters, the performance of the STFSC device was improved in terms of the open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and efficiency (ƞ). Furthermore, the power conversion efficiency (PCE) of the STFSC device with and without CuO plasmonic nanoparticles correspond to 10.27 % and 15.57 % respectively. The increased light absorption was due to the effect of the larger surface area of the CuO plasmonic nanoparticles in the p-CuO absorber layer which increased light absorption and subsequently increasing the photocurrent.